Prevalence of BRCA1/2 germline mutations in 21 401 families with breast and ovarian cancer - Kast, Karin; Fischer, Christine; Dikow, Nicola; Schott, Sarah (Journal of medical genetics, 2016)
Purpose To characterise the prevalence of pathogenic germline mutations in BRCA1 and BRCA2 in families with breast cancer (BC) and ovarian cancer (OC) history. Patients and methods Data from 21 401 families were gathered between 1996 and 2014 in a clinical setting in the German Consortium for Hereditary Breast and Ovarian Cancer, comprising full pedigrees with cancer status of all individual members at the time of first counselling, and BRCA1/2 mutation status of the index patient. Results The overall BRCA1/2 mutation prevalence was 24.0% (95% CI 23.4% to 24.6%). Highest mutation frequencies were observed in families with at least two OCs (41.9%, 95% CI 36.1% to 48.0%) and families with at least one breast and one OC (41.6%, 95% CI 40.3% to 43.0%), followed by male BC with at least one female BC or OC (35.8%; 95% CI 32.2% to 39.6%). In families with a single case of early BC (<36 years), mutations were found in 13.7% (95% CI 11.9% to 15.7%). Postmenopausal unilateral or bilateral BC did not increase the probability of mutation detection. Occurrence of premenopausal BC and OC in the same woman led to higher mutation frequencies compared with the occurrence of these two cancers in different individuals (49.0%; 95% CI 41.0% to 57.0% vs 31.5%; 95% CI 28.0% to 35.2%). Conclusions Our data provide guidance for healthcare professionals and decision-makers to identify individuals who should undergo genetic testing for hereditary breast and ovarian cancer. Moreover, it supports informed decision-making of counselees on the uptake of genetic testing.
Gesehen am 12.03.2018